2018
DOI: 10.1080/14737167.2018.1479254
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating quantity and quality of literature focusing on health economics and pharmacoeconomics in Gulf Cooperation Council countries

Abstract: The use of economic evaluation studies in G.C.C was limited. Different factors that affect the quality of articles such as performing a full economic evaluation and choosing societal perspective were identified. Strategies to improve the quality of future studies were recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…Nevertheless, 27 studies overlapped, and 23 studies were included in our review, which were potentially eligible yet not included in previous reviews. Overall, from 535, 3074, and 1950 citations, Al-Aqeel et al, [37] Eljilany et al, [4] and Farid et al [5] identified 15 (2.8%), 49 (1.6%), and 15 (0.7%) eligible studies, to which our review could potentially add 4, 11, and 12 more. Our study yielded 105 eligible articles from 1646 citations (6.4%), while it missed at least 26 studies, suggesting that the sensitivity of our search strategy needs to be further developed.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Nevertheless, 27 studies overlapped, and 23 studies were included in our review, which were potentially eligible yet not included in previous reviews. Overall, from 535, 3074, and 1950 citations, Al-Aqeel et al, [37] Eljilany et al, [4] and Farid et al [5] identified 15 (2.8%), 49 (1.6%), and 15 (0.7%) eligible studies, to which our review could potentially add 4, 11, and 12 more. Our study yielded 105 eligible articles from 1646 citations (6.4%), while it missed at least 26 studies, suggesting that the sensitivity of our search strategy needs to be further developed.…”
Section: Discussionmentioning
confidence: 85%
“…Although our study involved most countries and the largest number of studies from MENA, health economic studies from the region have previously been reviewed in high-quality systematic reviews. Al-Aqeel et al [37] identified 15 health economic studies in KSA up to May 2011, Eljilany et al [4] reviewed 49 studies from countries of the Gulf Cooperation Council (Bahrain, KSA, Kuwait, Oman, Qatar, and UAE) until the end of 2017, and Farid et al [5] reviewed 15 studies from Egypt published between 2002 and 2017. While we included only studies that compared alternatives, previous reviews also included studies describing a single technology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A foundational step in designing capacity development programmes is to conduct a needs assessment, understood as "the systematic study of a problem or innovation, incorporating data and opinions from varied sources, in order to make effective decisions or recommendations about what should happen next" [6]. Available reviews of the health economic literature conducted in the region, be they with a cross-country [7,8] or single-country focus [9,10], all suggest a limited use of economic evaluation and substantial scope for improving methodological quality. There are also indications that most pharmacy schools offer pharmacoeconomics courses as part of their curriculum, albeit with widely varying hours and topics [11].…”
Section: Introductionmentioning
confidence: 99%